Perlindungan Hukum terhadap Kreditur dalam Pelaksanaan Pendaftaran Hak Tanggungan secara Elektronik - Khalisha Nabila Winanti; Noor Saptanti (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
This research explains the procedure for implementing electronic mortgage registration and discusses legal protection for creditors in mortgage registration through SKMHT in the event of the principal's death. This normative legal research utilizes a prescriptive approach based on legislation, cases, and conceptual analysis Primary data sources include relevant laws and regulations related to mortgages, supplemented by interviews with Notaries and PPAT, as well as secondary legal materials such as books, legal research papers, and previous studies in the form of journals, theses, and dissertations related to the research. Data collection techniques are carried out through interviews, observations, and literature studies Meanwhile, the analysis technique used by the author is qualitative model. The research results indicate that electronic registration of Mortgage Rights is carried out by interested parties through the website https://mitra.atr.bpn.go.id. However, in practice, there are still shortcomings in electronic Mortgage Rights registration, particularly when it is registered using SKMHT (Power of Attorney to Burden Mortgage Rights), and then the certificate owner passes away, the registration of Mortgage Rights cannot be continued. The solution to this problem is to add an optional refinement formulation in the Electronic Mortgage Rights System that allows for the replacement of the Identity Card Number (NIK) of the grantor with the NIK of the recipient if the Mortgage Rights are registered first with a SKMHT.